WISATA KOTA KUPANG: KEPUASAN WISATAWAN BERDASARKAN INDIKATOR SAPTA PESONA - Marpaung, Tiarma; Snae, Alfred; Hetharia, Gabriela Elysia; Angelika, Febiola (STABN Raden Wijaya Wonogiri, 2025)
As a tourist destination center in the capital of East Nusa Tenggara Province, Kupang City has several types of popular tourist destinations. Spread across six sub-districts, tourist destinations in Kupang City that are the object of this research are: 1) Warna Nunsui Beach in Kelapa Lima, 2) Monkey Cave in Alak, 3) Japanese Monument in Maulafa, 4) Ketapang Beach in Kota Lama, 5) NTT State Museum in Oebobo, and 6) Arjuna Park in Kota Raja. In addition, the quality of each tourist attraction in Kupang City is also researched based on the Sapta Pesona indicator. This qualitative research aims to explore information and perceptions of tourists who have visited or are visiting tourist sites in Kupang City through surveys. The seven indicators of Sapta Pesona consist of elements of safety, order, cleanliness, coolness, beauty, friendliness, and memories. The survey results show that the tourist charm in Kupang City provides sufficient satisfaction for tourists in the six tourist attractions in six sub-districts. In addition, the results of this survey can also be used as a reference for tourist site managers and the government through the local tourism office for the evaluation process and efforts to improve the quality of services and management of popular tourist objects in Kupang City in order to meet the standards and indicators of Sapta Pesona.